Suure õhtuteenistuse sissekäigu allegoorilis-sümbolistlik tõlgendus vene õigeusu traditsioonis - Burghardt, Anne (Usuteaduslik Ajakiri, 2011)
Allegorical Explanation of the Entrance During the Great Vespers in the Russian Orthodox Church The article gives an overview of the main works using an allegorical explanation of the liturgy of hours in the Russian Orthodox Church focusing on the explanation of the Entrance during the Great Vespers. An introductory part of the article presents a relevant explanation by the late Byzantine author Symeon of Thessaloniki from the beginning of the 15th century as his work De sacra precatione influenced the most the tradition of allegorical explanation of the liturgy of hours in the Russian Orthodox Church. The first genuine explanation of the Great Vespers in the Russian Orthodox Church was given by Feodosij Safanovic in the end of the 17th century. The 18th century was the period in the Russian Orthodox Church that lacked liturgical explanations due to the rationalising spirit of the time. A certain exception was an explanation of both the Divine Liturgy and the liturgy of hours written by Gavriil (Petrov) in the end of the 18th century. Although this work does not use an allegorical explanation, it is still shortly presented in the article in order to give a continous picture of the period preceding the 19th century, when the allegorical explanation of the liturgy of hours strongly prevailed in the Russian Orthodox Church. Concerning the 19th century, special attention is paid to the work Novaja Skrižal` ili Položitel`noe ob`jasnenie o Cerkvi, o liturgii, o vsech službach i utvarjach cerkovnych (1803), written by the archbishop Veniamin (Rumovskij-Krasnopevkov). This work was influenced by Euchologion by Jacques Goar, published in Paris in 1647, whereas Veniamin’s work itself had a big impact on most of the later allegorical explanations of the liturgy of hours and consequently also of the Great Vespers and its Entrance in the Russian Orthodox Church. The present article offers an overview of the most popular allegorical commentaries and their explanation of the Entrance during the Great Vespers, published in Russia during the 19th and in the beginning of the 20th century. As in the end of the 20th century reprints of the earlier works from the previously mentioned period have mostly been published in the Russian Orthodox Church, this article does not pay any special attention to the last decades of the passed century. Concerning the allegorical explanation of the Entrance during the Great Vespers, there are some common traits in all allegorical commentaries in the Russian Orthodox Church. In the first place, the explanation resembles very much to the one explaining the sense of the Small Entrance during the Divine Liturgy. Practically all authors explain the Entrance during the Great Vespers resp liturgical movements of a priest as a concentrated representation of redemption of humankind through Christ, from His incarnation to His Ascension. The article also makes an assertion that as long as the allegorical explanation does not overshadow the intension of the liturgical texts and the eschatological aspect is taken into account, helping to avoid the experience of the service as a „sacred play“ of the clergy, the allegorical explanation might support the kerygma of Christ in a practical liturgical context.